Pengaruh Metode Eklektik Terhadap Hasil Belajar Maharah Kalam - Rosilun Sururoh; Ahmad Mufarih Hasan (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2021)
Learning is communication between teachers and students in realizing or achieving good learning. This study focuses on the eclectic method of learning outcomes of speaking skill. The eclectic method can be interpreted as a mixed method, or in Indonesian it is called the method of choice. In Arabic terms it is called thoriqoh Intiqoiyyah. This study uses quantitative methods with product moment techniques to test the validity of the data and to find the reliability of the data using the alpha formula. While the hypothesis test using the F test and T test, then using the regression model. This study concludes that the eclectic method has a good influence on student learning outcomes. Meanwhile, other factors may also have the opportunity to influence student learning outcomes, both in terms of other methods or in terms of the quality of teachers and others.